Dimensões e ambiências da paisagem permacultural do Rio Grande do Sul - Mayer, Licia Quoos (2023)
This study explores the implementation of permaculture principles in Rio Grande do Sul state, South Brazil, focusing on its sustainable and integrated landscape planning methods. Permaculture combines ecological vision with principles and ethics that integrate traditional wisdom and technologies. Given the pressing environmental concerns and the demand for new design standards, permaculture emerges as a potential solution. However, a systematic examination revealed a scarcity of research on permaculture in postgraduate programs in architecture and urbanism across the country. Additionally, professionals in the field exhibit limited knowledge and practical application of permaculture techniques, indicating a knowledge gap that this study aims to address. The main objective of this research is to investigate the characteristics and contexts of permaculture landscapes in Rio Grande do Sul. A qualitative multimethod approach was employed, incorporating a literature review and interviews. Thirteen permaculture sites in the state were surveyed using a questionnaire, and two case studies were conducted: the Arca Verde Institute in São Francisco de Paula and Terra da Árvore Redonda (Tear Permacultura) in Vacaria. The findings were visualized through charts and schematic maps, providing general and specific information on the implementation of permaculture techniques and solutions in each site. Furthermore, location maps depicting the landscape's compositional elements and permacultural zoning were generated, facilitating a comparative and in-depth analysis of the two scenarios. The results indicate that permaculture offers innovative solutions for the creation of resilient and productive spaces. However, it is crucial to strengthen the permaculture network within the state to enable widespread application of this concept.